Use of the dance pad for the development of rhythmic abilities - Svobodová, L.; Skotáková, A.; Hedbavny, P.; Vaculiková, P.; Sebera, M. (Science of Gymnastics Journal, 2016)
In our research we assessed the effect of an intervention programme based on regular use of the dance pad on the level of rhythmic abilities as important factors influencing the performance in gymnastic sports, dancing, figure skating and so on. The sample consisted of 28 dancers aged between 8-13 years. The tested persons were divided into 2 groups according to age and length of dance practice. Each group was then divided into experimental and control group. Experimental groups were asked to dance on the dance pad 3 times a week for two and a half months. The level of rhythmic perception was measured by the test of rhythmic discrimination by Seashore. The level of rhythmic execution was measured by the test Software reaction meter and Hands and feet drumming. For data analysis of rhythmic abilities we chose descriptive statistics and T-test, calculation of Cohen's d coefficient and Spearman rank correlations. Although the research did not confirm positive influence of dance pad on the development of rhythmic abilities of the tested persons, more options to investigate were shown.